Effect of sugar and amino acids on growth and survival of Arcobacter butzleri in high saline medium - Červenka, Libor; Machačová, Irena (University of Pardubice, 2011)
The study of effect of sugars and amino acids on the growth and survival of fourstrains mixture of Arcoabcter butzleri in tryptic soy broth (TSB) with different salt concentrations was carried out at 30 °C. A. butzleri was able to grow in TSB with 3.5 % NaCl whereas no viable counts were detected at 4.0 and 5.0 % after 0.5-day incubation. Sucrose, trehalose, alanine, glutamine or proline at 0.25 mmol levels were separately added to TSB with 3.5 % NaCl. The growth and survival parameters were estimated according to Baranyi and Weibull model, respectively. The growth of A. butzleri was affected by all the amino acids resulting in higher growth rate, lag phase and maximum population density in medium with 3.5 % NaCl. Slight increase in growth rate in the presence of sucrose and trehalose was only observed. On the other hand, bacteria better survived when sugars were used, increasing the first reduction time (δ). Comparing the results with TSB with natural content of NaCl (0.5 %), only sucrose enhanced the growth of A. butzleri, whereas both sugars and amino acids improved their survival resulting in higher δ.